2000
DOI: 10.1063/1.1289685
|View full text |Cite
|
Sign up to set email alerts
|

The two-plasmon decay of an extraordinary electromagnetic wave in a magnetized homogeneous plasma

Abstract: The effects of the presence of a uniform magnetic field on the growth rate and the threshold intensity of the two-plasmon decay in a homogeneous plasma have been investigated. Analytical expressions for the growth rate and threshold intensity have been obtained. It has been shown that the presence of a magnetic field affects significantly the growth rate and the threshold intensity for the two-plasmon decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Shukla [23] showed that a short, extraordinary polarized laser pulse can generate a large-amplitude upper hybrid wake wave in magnetized plasma. Laham et al [16] considered the decay of an extraordinary wave into two electrostatic waves at frequencies close to the upper hybrid frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shukla [23] showed that a short, extraordinary polarized laser pulse can generate a large-amplitude upper hybrid wake wave in magnetized plasma. Laham et al [16] considered the decay of an extraordinary wave into two electrostatic waves at frequencies close to the upper hybrid frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This finds application in the fast ignition scheme in inertial confinement fusion (ICF), where quasistable self generated magnetic fields may be present in the underdense corona region close to the critical surface of the ignition pulse [13]. However, the effect of such fields on parametric processes in laser produced plasmas has not been widely examined even though there are a good many general papers on the three wave interactions in magnetized plasmas [14][15][16][17]. Recently, Krasovitskiy et al [18] investigated the efficiency of electron acceleration by a short, powerful laser pulse propagating across an external magnetic field and analyzed the conditions for the decay of a laser pulse with frequency close to the upper hybrid resonance frequency.…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical analysis based on the linear (with respect to the amplitude of the pump wave) growth rates of parametric instabilities [2][3][4][5][6][7] describes only the initial stage of decay and fails to provide infor mation on the interaction of finite amplitude wave packets with plasma. The strongly nonlinear stage of the parametric decay of the original wave and the non linear saturation of the secondary wave in plasma can be analyzed using numerical simulation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of laser energy conversion into the thermal energy of plasma electrons is the Raman or two plasmon decay, accompanied by the excitation of an upper hybrid quasi potential wave [3][4][5][6]. In cold plasma, an extraordinary electromagnetic wave decays into two half frequency waves [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that at the laser power flux used for laser plasma interaction, parametric instabilities, such as the stimulated Raman scattering ͑SRS͒, 1-4 stimulated Brillouin scattering ͑SBS͒, 5,6 selffocusing/filamentation instability, [7][8][9][10] and the two-plasmon decay instability, [11][12][13] take place. It is well known that at the laser power flux used for laser plasma interaction, parametric instabilities, such as the stimulated Raman scattering ͑SRS͒, 1-4 stimulated Brillouin scattering ͑SBS͒, 5,6 selffocusing/filamentation instability, [7][8][9][10] and the two-plasmon decay instability, [11][12][13] take place.…”
Section: Introductionmentioning
confidence: 99%